The Gamification of Compliance: A Critical Analysis of ClassDojo and Behavior Apps as the Modern Educational Panopticon - Sri Andayani (STIT Pringsewu, 2025)
This study critically examines the widespread adoption of gamified behavior management applications in contemporary education, utilizing ClassDojo as a primary case study to explore the intersection of surveillance technology and behavioral psychology. Drawing upon Michel Foucault’s concept of the Panopticon and B.F. Skinner’s operant conditioning framework, the research analyzes how these platforms function as digital surveillance infrastructures that normalize continuous monitoring and the datafication of student conduct. Through a qualitative library-based research methodology, the study synthesizes interdisciplinary scholarship to demonstrate that while these tools are marketed as fun engagement strategies, they operate as sophisticated disciplinary mechanisms that erode intrinsic motivation and cultivate performative compliance. The findings reveal that the gamification of behavior substitutes moral reasoning with point-scoring, transforms peers into co-surveillants via public leaderboards, and habituates children to the extractive logic of surveillance capitalism. The paper concludes that the uncritical integration of such technologies threatens to reshape the educational environment into a training ground for the surveillance state, necessitating a re-evaluation of the ethics of educational technology.